Effects of local application of bovine amniotic fluid on fracture healing in rats ( Rattus norvegicus ) - Tanrisever, Murat; Istek, Ozmen; Eroksuz, Natice; Karabulut, Burak; Ozcan, Erhan Cahit; Bingul, Muhammet Bahattin; Guler, Ridvan (Univ Zulia, Facultad Ciencias Veterinarias, 2024)
In this study, it was aim to examine the local application of bovine amniotic fluid on bone fracture healing in rats. Twenty female sprague dawley rats included in the study were divided into 2 groups of 10. The sham group (n=10): Bone fractures were created in the right tibia bones of the rats and fixed with kirschner wire. After a four-week recovery period, the subjects were sacrificed. Local bovine amniotic fluid group (n=10): Bone fractures were created in the right tibia bones of the rats and local bovine amniotic fuid was applied during fixation with kirschner wire. After a four-week recovery period, the subjects were sacrificed. Samples from all subjects were decalcified, stained with hematoxylin and eosin, and new bone formation and fibrosis were analyzed. When the groups were evaluated in terms of new bone regeneration, it was determined that the new bone regeneration in the subjects treated with local bovine amniotic fluid were statistically significantly higher than sham group ( P <0.05). When the groups were evaluated in terms of fibrosis, the fibrosis value in the sham group was found to be statistically significantly higher when compared with the local bovine amniotic fluid group ( P <0.05). It can be stated that local bovine amniotic fluid application may positively affect the healing of bone fractures.
Keywords: Bovine amniotic fluid; bone fracture; local application; bone fracture healing